pengaruh penggunaan membaca berulang-ulang terhadap pemahaman membaca siswa - Muhammad Nasir; Widya Syafitri; Loli Safitri (ELP (Journal of English Language Pedagogy), 2022)
This study was intended to find out the effectiveness of repeated reading strategy toward students’ reading comprehension. This quantitative research done due to some problems found during reading class. First, the teacher used the conventional strategy since the teacher acted as the center of the class. Then, the students showed a little comprehension in reading, such as finding the main idea, reference, or inference of the text. Last but not least, the teacher admitted that the students often doubt about finding out the moral value of the text, because it was not written on the text. After doing treatment by implementing repeated reading strategy, researcher found that students’ reading comprehension was improved. It was showed that t-obtained was higher than t-table (6,872>2,064). Hence, there is a significant effect of repeated reading strategy toward student reading comprehension.